THE ROLE OF MADRASAH SUPERVISORS IN THE IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM - Djubu, Herlina (Jurnal Impresi Indonesia, 2023)
The aim of writing this article is to obtain an overview of the role of madrasah supervisors in implementing the independent learning curriculum. Implementation of the Independent Curriculum is voluntary, gradual according to ability, and depends on the readiness of each educational unit. In its implementation it is certainly not easy, especially raising awareness of each madrasah (educator) in implementing the independent learning curriculum, so madrasah supervisors have a strategic role in influencing, encouraging, directing, guiding and mobilizing madrasah residents, therefore the role of supervisors is as regulated in GTK Director General Regulation No. 4831 of 2023 The Role of School Supervisors in the Independent Learning Policy, is the basis on which a supervisor plays his role in implementing the independent learning curriculum in educational units. The conclusion of writing this article shows that: (1) Madrasah supervisors carry out the role of supervisors and leaders of change in their educational institutions, (2) The independent learning curriculum is student-centered educational program planning, where educational units have autonomy in developing their curriculum, (3 ) Madrasah supervisors have a strategic role in the curriculum development process.